The structure and evolution of lithosphere of the central part of the northwestern shelf of the Black Sea - M.V. Kozlenko; Yu.V. Kozlenko (Геофизический журнал, 2014)
Density modeling has been conducted that made possible to specify the structure of lithosphere of the central part of northwestern shelf of the Black Sea.In the section of the profile the boundary between the East European platform and the Scythian plate has been identified, which is the fault inclined southward and located in the upper part of the section about 30km northward of the Golitsyn fault. On the base of the plotted paleostructural section evolution of Scythian plate in the crossec-tion of the profile since Paleozoic has been traced. The basement of northwestern shelf of the Black Sea and its central part was broken by numerous disjunctives and fault zones, many of them can be traced within sedimentary cover and stretch to the lower levels of crystal crust.